Antioxidant enzymes and association of CAT SNP‐21 A/T (rs7943316) with male infertility. Issue 9 (23rd August 2021) - Sadia, Khulah; Sultan, Sikandar; Khan, Kifayatullah; Javeres, Leonel M.; Rumman, Baseerat; Shah, Syed T. A.; Batool, Sajida; Nurulain, Syed M.
Abstract: Infertility is a multifactorial and polygenic disease. A vast majority of infertility is still unexplained despite modern diagnostic techniques. Oxidative stress is considered a factor for male infertility but etiology in terms of functional gene polymorphism and experimental studies on human subjects is scarcely reported. The aim of the study was to investigate the status of three antioxidant enzymes; catalase, superoxide dismutase (SOD), and glutathione reduced (GSH) in clinically diagnosed infertile males and find the potential association of CAT gene variant in the promoter region −21 A/T (rs7943316). The study consisted of 55 clinically diagnosed infertile males and 50 non‐infertile volunteers. The activity of antioxidant enzymes was measured through a spectrophotometer. Polymerase chain reaction–restriction fragment length polymorphism was performed for genotyping of single‐nucleotide polymorphism. Catalase enzyme activity was significantly decreased while SOD and GSH were substantially increased ( p  ≤ 0.01) in infertile men in comparison to non‐infertile. CAT gene variant rs7943316 had shown significant association in dominant, recessive model and allelic frequencies. The study concludes that rs7943316 has a substantial role in male infertility. The outcome of the study may help in resolving idiopathic infertility cases and may help in evolving novel diagnostic and therapeutic approaches. Other variants of CAT and antioxidant genes are suggested to ascertain further insight.